Causes and Treatment of Birth Trauma-Related Femoral Fracture: A Longitudinal Study - Abdul Rahman Khan, Azizullah, Muhammad Shuaib Chandio, Zulfiqar Ali Jatoi, Sajjad Hussain Bhatti, Sartaj Lakhani, Niaz Hussain Keerio, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the causes and treatment of birth trauma related femoral fractures. Study design: A longitudinal study Place and Duration: This study was conducted at DIMC, Dow University of Health Sciences, Karachi from January2021 to January 2022. Methodology:The study included cases of femoral fractures in neonates caused by birth trauma. The cases of birth histories were investigated in terms of gestational age, birth weight,and mode of delivery. The category of femoral fracturesand the treatment performed were both noted. Cases were followed until they were recovered.A comprehensive clinical examination was performed. Other birth traumas, fractures, nerve palsies, and/or symptoms of other musculoskeletal, genetic diseases, such as blue sclera and hypermobile joints (osteogenesis imperfecta), were noted. Results:A total of 15 newborns with femoral fractures were included in this study.The average gestational age was 38.2 weeks, with an average diagnosis time of 3 days. In the majority of cases, the infant was born breech and delivered via Caesarean section. Eleven instances had mid-shaft fractures, while four had subtrochanteric fractures. After an average of 3.1 weeks, all patients had a complete union. Conclusion:A femoral fracture in a neonate due to birth related trauma is quite uncommon. It occurs more frequently in Caesarean sections performed for breech presentation. Preterm and/or low birth weight newborns are at a higher risk. The femur shaft is commonly fractured. The prognosis for these fractures is excellent, and they heal completely after immobilization. Keywords: Birth Trauma, Femoral Fracture, Management, Risk Factors